(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Skin disorders are most common occurring diseases in places where humidity prevails throughout the year. Vicharchika and Eczema both having resemblance in set of their clinical signs. Rasapushpadi Malhara (RPM) is Rasa preparation described in Rasa tarangini which is indicated in some skin disorders like Phirang, Vrna, Vicharchaika etc. In present study two samples of Rasa Pushpa (RP) has been prepared by two methods i.e. Kupipakva method and Damru yantra method. Both the samples were further used to prepare two samples of Rasapushpadi Malhara using Siktha taila as base and ratio of Siktha & Til taila was taken in ratio of 1: 5 according to the season. The randomized control clinical trial was carried out in between two groups. Both groups showed significant results on different clinical parameters like Kandu, Daha, Srava, Rukshta, Pidika, Vaivaranyata, Pidika, Raji, but group B showed highly significant result in EASI Score, which indicates severity of eczema. Level of significance in Group B for EASI Score is, P<0.00001. Rasapushpadi Malahara is very potent in treatment of Vicharchika as it contains mineral and herbal drugs like Parada, Kasisa, Saindhava, Sphatika, Wax, Tila taila, all having good antibacterial and antifungal properties. So this formulation showed significant results only by external application.